2015
DOI: 10.1186/s41038-015-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

Cadaveric bone marrow mesenchymal stem cells: first experience treating a patient with large severe burns

Abstract: BackgroundIn January 2005, Rasulov et al. originally published “First experience in the use of bone marrow mesenchymal stem cells (MSCs) for the treatment of a patient with deep skin burns”. Here, we present the first ever treated patient with cadaveric bone marrow mesenchymal stem cells (CMSCs) in the history of Medicine.MethodsA young man, who severely burned 60 % of his total body surface with 30 % of full-thickness burns while working with a grass trimmer that exploded, was involved in the study. MSCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 14 publications
0
26
0
3
Order By: Relevance
“…Currently, a series of clinical trials (1 allogenic MSC, 1 cadaveric MSC, 1 bone marrow MSC) and a casecontrol prospective study (bone marrow MSC = 20, umbilical cord-MSC = 20, EE&G = 20) investigating the efficacy and safety of stem cell therapy have been completed. The results demonstrate that MSCs can effectively promote burn wound healing and are considered safe and effective, with great therapeutic potential for patients with severe burns [20][21][22][23]. However, to date, there has been no systematic and comprehensive preclinical analysis of stem cell therapy for burn wounds, and the integration of these preclinical data can offset knowledge gaps that may affect the future application of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a series of clinical trials (1 allogenic MSC, 1 cadaveric MSC, 1 bone marrow MSC) and a casecontrol prospective study (bone marrow MSC = 20, umbilical cord-MSC = 20, EE&G = 20) investigating the efficacy and safety of stem cell therapy have been completed. The results demonstrate that MSCs can effectively promote burn wound healing and are considered safe and effective, with great therapeutic potential for patients with severe burns [20][21][22][23]. However, to date, there has been no systematic and comprehensive preclinical analysis of stem cell therapy for burn wounds, and the integration of these preclinical data can offset knowledge gaps that may affect the future application of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…31 In the case of extensive, deep burns (3 rd degree), the use of stem cells is recommended. 32,33 At present, we can agree that the CEA transplant is a life-saving, but expensive procedure, unsuitable for the permanent coverage of burn wounds deeper than the 2 nd degree. 34 Matters related to the optimal donor site selection for cell culture purposes, wound dressing applied to the wound before harvesting the donor skin for the culture and post-cell transplantation, and, most importantly, an informed choice of the group of patients for whom applying keratinocytes will give a maximum clinical effect, should have all been systematized many years ago.…”
Section: Discussionmentioning
confidence: 96%
“…To surmount the barriers associated with MSC precedence and isolation procedures, the use of cadaveric MSCs (CMSCs) from BM has recently emerged as a new approach. Mansilla and coworkers were the first research group that reported the use of CMSCs for treating severe thermal burns in a 26-year old male patient [24]. After isolation and expansion of CMSCs, combined treatment (conventional and CMSCs) was administered to the patient, who did not have any immunological rejection and was monitored during 35 days.…”
Section: Introductionmentioning
confidence: 99%